Relato de experiências da construção de minhocário caseiro como prática de educação ambiental - Barros, Carlos Eduardo [UNESP]; Perusi, Maria Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The current problem of municipal solid waste (MSW) and its disposal have generated several debates due to the contamination of natural resources, especially soil and water. Some alternatives to minimize the negative impacts are recycling and composting. The present work reports environmental education experiences, through the construction of a Worm farm, low cost, in an attempt to enlighten and sensitize the community members involved: goers of “Casa da Santa Luz”, group of studies scientific/social and cultural and shamanic spiritual practices in Assis/SP, freshman the Geography Course UNESP/Ourinhos and settlers of the Sustainable Development Project "Prof. Luiz D. Macedo" in Apiaí/SP, how much the responsibility and participation in solid waste management. Thus, it was collectively built one worm farm with gallons of water 20 liters for household waste composting purposes. As a result, it became popular the use of domestic worm farm; promoted the debate about environmental issues and it is intended that this way, there is the incorporation of new practices in the everyday life of citizens, to avoid negative effects on the environment.

O problema atual dos resíduos sólidos urbanos (RSU) e sua disposição têm gerado diversos debates por conta da contaminação dos recursos naturais, principalmente do solo e água. Algumas alternativas para minimizar os impactos negativos são a reciclagem e a compostagem. O presente trabalho relata experiências de educação ambiental, através da construção de um minhocário caseiro, de baixo custo, na tentativa de esclarecer e sensibilizar os membros da comunidade envolvida: frequentadores da “Casa da Santa Luz”, grupo de estudos científicos/socioculturais e práticas espirituais xamânicas em Assis/SP; calouros do Curso de Geografia UNESP/Ourinhos e assentados do Projeto de Desenvolvimento Sustentável Prof. Luiz D. Macedo em Apiaí/SP, quanto a responsabilidade e participação na gestão dos resíduos sólidos. Para tanto, coletivamente foi construído um minhocário com galões d’água de 20 litros, para fins de compostagem de resíduos domésticos. Como resultado, popularizou-se o uso do minhocário doméstico; fomentou-se o debate acerca da problemática ambiental e pretende-se que assim, haja a incorporação de novas práticas no cotidiano dos cidadãos, para evitar efeitos negativos sobre o meio ambiente.
Keywords: Composting; Municipal solid waste; Environmental education; Compostagem; Resíduos sólidos urbanos; Educação ambiental